The Influence of Online Customer Reviews, Brand Trust, and Gender on Product Purchasing Decisions - Matthew Christopher Setiadjaja; Ignatius Ario Sumbogo (Universitas Pelita Harapan, 2024)
This research aims to determine and analyze the influence of price perceptions, online customer reviews, and brand image on purchasing decisions for Converse shoes on Shopee e-commerce. Using multiple linear regression analysis with IBM SPSS Statistics 26 as an analysis tool. The sample used was users and prospective users of Converse shoes domiciled in DKI Jakarta who purchased the Shopee e-commerce application with a total of 153 respondents. Survey via Google Forms online and using a Likert scale. The sampling technique is non-probability sampling with a purposive sampling method. The results show that price perception, online customer reviews, and brand image partially influence the decision to purchase Converse shoes on Shopee e-commerce. Price perception, online customer reviews, and brand image simultaneously have a significant influence on the decision to purchase Converse shoes on Shopee e-commerce.